2019
DOI: 10.7459/ept/41.2.02
|View full text |Cite
|
Sign up to set email alerts
|

Science Classroom Learning Environments in Afghanistan: Assessment, Effects and Determinants

Abstract: Although the field of classroom learning environments has undergone remarkable expansion and internationalisation, no study in Afghanistan in any subject area or at any educational level has ever adopted a learning environment framework or involved the assessment and investigation of classroom environments. Our study in Afghanistan included seven learning environment scales from the widely-used What Is Happening In this Class? (WIHIC) questionnaire, together with two scales assessing the student attitudes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 120 publications
0
2
0
Order By: Relevance
“…Learning environment research has provided consistent evidence to suggest that "students learn better when they view the classroom environment more positively" (Dorman and Fraser 2009, p. 78). Within the context of science education, numerous studies have reported that perceptions of the learning environment impact on a range of science outcomes (Fraser 2014), including enjoyment (see, for example, Aldridge & Bell, 2014;Sayed & Fraser, 2019;Peer & Fraser, 2015), self-efficacy (see, for example, Lee, Liang, Wu, Chiou, Hsu et al, 2020;Velaytham & Aldridge, 2013XX) and career aspirations (Khalil & Aldridge, 2019). Although some research has investigated the influence of learning environment perceptions on student motivation in countries such as Turkey (Kingir, Tas, Gok, & Vural, 2013), Australia and Africa (Opolot-Okurut, 2010;Schulze & van Heerdem, 2015), there is very limited research that investigates learning environment-motivation relationships in Arabic countries, and none that has focused on girls at the high school level.…”
mentioning
confidence: 99%
“…Learning environment research has provided consistent evidence to suggest that "students learn better when they view the classroom environment more positively" (Dorman and Fraser 2009, p. 78). Within the context of science education, numerous studies have reported that perceptions of the learning environment impact on a range of science outcomes (Fraser 2014), including enjoyment (see, for example, Aldridge & Bell, 2014;Sayed & Fraser, 2019;Peer & Fraser, 2015), self-efficacy (see, for example, Lee, Liang, Wu, Chiou, Hsu et al, 2020;Velaytham & Aldridge, 2013XX) and career aspirations (Khalil & Aldridge, 2019). Although some research has investigated the influence of learning environment perceptions on student motivation in countries such as Turkey (Kingir, Tas, Gok, & Vural, 2013), Australia and Africa (Opolot-Okurut, 2010;Schulze & van Heerdem, 2015), there is very limited research that investigates learning environment-motivation relationships in Arabic countries, and none that has focused on girls at the high school level.…”
mentioning
confidence: 99%
“…In Afghanistan, Sayed & Fraser (2019) administered a Dari translation of one SALES scale (namely, Self-regulation) to 1610 grade 10-12 science students in a range of school sizes and of various ethnic and social groups. All schools were single-gender because there is no co-education in Afghanistan.…”
Section: Attitudesmentioning
confidence: 99%